Fusarium graminearum Trichothecene Mycotoxins: Biosynthesis, Regulation, and Management - Chen, Yun; Kistler, H Corby; Ma, Zhonghua (Annual review of phytopathology, 2019)
Fusarium head blight (FHB) of small grain cereals caused by and other species is an economically important plant disease worldwide. infections not only result in severe yield losses but also contaminate grain with various mycotoxins, especially deoxynivalenol (DON). With the complete genome sequencing of , tremendous progress has been made during the past two decades toward understanding the basis for DON biosynthesis and its regulation. Here, we summarize the current understanding of DON biosynthesis and the effect of regulators, signal transduction pathways, and epigenetic modifications on DON production and the expression of biosynthetic genes. In addition, strategies for controlling FHB and DON contamination are reviewed. Further studies on these biosynthetic and regulatory systems will provide useful knowledge for developing novel management strategies to prevent FHB incidence and mycotoxin accumulation in cereals.